2018
DOI: 10.1016/j.joca.2018.02.373
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics and metabolic function analysis of the secretome of articular cartilage and isolated chondrocytes in response to pro-inflammatory cytokines

Abstract: Purpose: Chondrocytes rely primarily on glycolysis to meet their energy requirements, but possess the metabolic flexibility to support cell survival and matrix synthesis during periods of nutrient stress, by enhancing glycolysis with mitochondrial respiration. Accessing this 'spare respiratory capacity' requires optimal mitochondrial function, but since impaired mitochondrial function is implicated in osteoarthritis (OA), this mechanism may be deficient or attenuated in joint disease. Metabolic adaptation is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Previously, an in vivo study of equine OA identified physiological levels of TNF-α and IL-1β within SF to be 40–80 pg/mL . However, our study, along with previous studies in the field, has used significantly higher cytokine concentrations to experimentally model OA. ,, This approach was used within this study due to the short half-lives of these two cytokines. , Supplementation at a concentration closer to the physiological levels would have ultimately resulted in the experiment being largely conducted with cytokine levels significantly below that experienced during OA, thus producing results that may have been of insufficient benefit. Therefore, the approach used within this study to model OA should be taken into consideration when interpreting the results.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Previously, an in vivo study of equine OA identified physiological levels of TNF-α and IL-1β within SF to be 40–80 pg/mL . However, our study, along with previous studies in the field, has used significantly higher cytokine concentrations to experimentally model OA. ,, This approach was used within this study due to the short half-lives of these two cytokines. , Supplementation at a concentration closer to the physiological levels would have ultimately resulted in the experiment being largely conducted with cytokine levels significantly below that experienced during OA, thus producing results that may have been of insufficient benefit. Therefore, the approach used within this study to model OA should be taken into consideration when interpreting the results.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, elevations in glutamate were identified within the culture media at 3−5 days, consistent with a previous study, which may be resultant of the catabolism of collagenous proline through proline oxidase. 27,95 Reduced levels of collagen type VI α 2 chain and collagen type X α 1 chain were identified at 3−5 and 6−8 days following cytokine treatment. This may reflect a reduction in collagen synthesis, which has previously been identified within other collagen types following TNF-α/IL-1β stimulation.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations